Prevalence of polypharmacy and potential drug-drug interactions associated with risk factors in the era of hiv integrase inhibitors: A prospective clinical study - YAĞÇI ÇAĞLAYIK, DİLEK; TİGEN, ELİF; SİLİ, ULUHAN; ERTÜRK ŞENGEL, BUKET; KORTEN, VOLKAN (My University, 2023)
People living with human immunodeficiency virus (PLWH), with the availability of modern antiretroviral drugs, have multiple comorbidities, which increase the risk of polypharmacy and potential drug-drug interactions (PDDIs). This is a particularly important issue for the aging population of PLWH. This study aims to review the prevalence and risk factors for PDDIs and polypharmacy in the era of HIV integrase inhibitors. A cross-sectional, two-center, prospective observational study was conducted on Turkish outpatients between October 2021 and April 2022. Polypharmacy was defined as the use of >= 5 non-HIV medications, excluding over-the-counter (OTC) drugs, and PDDIs were classified using the University of Liverpool HIV Drug Interaction Database (harmful/red flagged and potentially clinically relevant/amber flagged). The median age of the 502 PLWH included in the study was 42 +/- 12.4 years and 86.1% were males. Most individuals (96.4%) were given integrase-based regimens (unboosted 68.7% and boosted 27.7%). In total, 30.7% of individuals were taking at least one OTC drug. The prevalence of polypharmacy was 6.8% (9.2% when OTC drugs were included). During the study period, the prevalence of PDDIs was 1.2% for red flag PDDIs and 16% for amber flag PDDIs. CD4(+) T cell count >500 cells/mm(3), number of comorbidities >= 3, comedication with drugs affecting blood and blood-forming organs, cardiovascular drugs, and vitamin/mineral supplements were associated with red flag or amber flag PDDIs. Drug interaction prevention is still important in HIV care. Individuals with multiple comorbidities should be closely monitored for non-HIV medications to prevent PDDIs.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Yaşam Bilimleri; Temel Bilimler; Social Sciences and Humanities; Sociology; Life Sciences; Natural Sciences; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); BULAŞICI HASTALIKLAR; İmmünoloji; Yaşam Bilimleri (LIFE); PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); INFECTIOUS DISEASES; IMMUNOLOGY; Life Sciences (LIFE); İş Sağlığı ve Terapisi; Güvenlik Araştırması; Sağlık (sosyal bilimler); Genel Sosyal Bilimler; Halk, Çevre ve İş Sağlığı; Bulaşıcı hastalıklar; Epidemiyoloji; Genel İmmünoloji ve Mikrobiyoloji; Sağlık Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; Occupational Therapy; Safety Research; Health (social science); General Social Sciences; Public Health, Environmental and Occupational Health; Infectious Diseases; Epidemiology; Immunology; General Immunology and Microbiology; Health Sciences; Social Sciences & Humanities; drug; drug interactions; HIV; modern antiretroviral therapy; polypharmacy; PEOPLE; OLDER; COMEDICATIONS; OUTCOMES; COHORT; ADULTS; MEN